Odpowiedź:
1.
3* (- 1/3)² - 6 * (-1/3)
3* 1/9 + 6/3 = 3/9+6/3 = 3/9+18/9 = 21/9 = 2 i 3/9 = 2 i 1/3
Odp B
2.
-6(3*(-2) + 8) = -6 ( -6+8)= -6* 2 = -12
Odp B
3.
a) 4 - 5* (-1) = 4 - ( -5) = 4+5= 9
b) 2* (-2)² - 7 (( 3* (-2)+2))=2 * 4 - 7 ( -6+2 ) = 8 - 7 * (-4) = 8+28 = 36
4.
a) 5a - 2 - 3 + 6 + 4a - 2 = 9a - 1 = 9 * (2) - 1 = -18-1=-19
b) 2x+3y+9-3x+2y = -x + 5y + 9 = -4 + 5* (-0,3 )+ 9 = -4 -1,5 + 9 = -5,5 + 9 = 3,5
5.
3x-4-3-x = 2x - 7
Odp B
6.
Mnożysz -3 z wyrazami w nawiasie i Ci wychodzi
-18a -9b
Odp D
7.
a-2b+3a-3b
4a - 5b
Odp A
Szczegółowe wyjaśnienie: